Effects of Dietary Local Hemp Seed Meal as Soybean Meal Alternative on Productive Performance, Egg Quality and Yolk Fatty Acid Composition of Laying Hens - Ozturk, Ergin; Darmawan, Arif; Ozlu, Sevket; Abaci, Samet Hasan (Taylor & Francis Ltd, 2024)
Supply problems and rising soybean meal prices have an impact on increasing feed costs. Hemp seed meal (HSM) with high protein content has the potential to be used as an alternative to soybean meal. This study evaluated the impact of dietary HSM of Narl & imath; Saray & imath; variety as a substitute for soybean meal on productive performances, egg quality and yolk fatty acid composition. A total of 120 Lohmann Brown laying hens aged 50 weeks were allocated into 4 groups and 10 repetitions. Birds received treatment without HSM (control group), or soybean meal substituted with 4%, 8% and 12% HSM. Dietary 4% significantly increased (p < 0.05) egg production and decreased FCR compared with 8% and 12% HSM group but did not differ from the control group in an overall period of 6 weeks. The inclusion of the 12% HSM group significantly decreased (p < 0.05) egg production. Meanwhile, there was no influence of hemp seed meal (p > 0.05) on feed intake, egg weight, body weight change, egg shape index, albumen index, albumen weight, Haugh unit, yolk weight, yolk index and eggshell thickness. Dietary 8% and 12% HSM significantly increased (p < 0.05) eggshell weight and yolk colour compared with control and 4% HSM groups. There was a significant increase (p < 0.05) in omega-3 fatty acid concentration and a decrease in yolk omega-6 to omega-3 fatty acids ratio with an increase in dietary HSM. It was concluded that dietary up to 12% HSM of the Narl & imath; Saray & imath; variety decreased egg production and increased FCR. Increasing dietary levels of HSM increased eggshell weight, yolk colour and omega-3 fatty acids content and decreased the omega-6 to omega-3 fatty acids ratio.
Ozturk, Ergin/0000-0002-6266-1117;
Keywords: Anti-Nutrient; Cannabis sativa L; Egg Production; Eggshell; Egg Quality; Fatty Acids